Changes in rainfall pattern affect crab herbivory rates in a SW Atlantic salt marsh - Alberti, Juan (2007)
Climatic fluctuations usually change the intensity of existing interactions. Thus, in the context of the global climate change, it is important to consider new potential interactions or changes that may appear. Heavy rainy periods (one of the consequences of global climate change in eastern-central Argentina) can promote flooding in some estuaries (mainly on coastal lagoons), and thus, affect interactions between species. In this work we investigate if climatic fluctuations can affect Spartina densiflora Brong. (dominant marsh plant) survival through a chain of biotic and abiotic interactions in a SW Atlantic costal lagoon (37° 40′S, 57° 23′W; Mar Chiquita, Argentina). To achieve this, the long-term rainfall behavior of this region, and the effect of rainy periods on submergence of estuarine marsh areas (using satellite images) were analyzed. Then, the effect of flooding on the activity of the dominant herbivore of this system, the burrowing crab Neohelice granulata (= Chasmagnathus granulatus), was studied using pitfall traps. Finally, the effect of flooding on crab herbivory rates and plant survival were analyzed using transplants, stem-marking and flooding experiments. Long-term rainfall behavior showed that mean annual rainfall has increased during the last century, with the occurrence of more rainy years, and increases in cumulative monthly rainfall increased the submerged area of the S. densiflora marsh. Also, crab activity in the marsh largely increased during periods of flooding, associated with more than 100% increments in herbivory rates and stem mortality. These results reveal that increments in rainfall regime can trigger a cascade of abiotic and biotic interactions leading to increased marsh mortality, and stresses the importance of considering both, biotic and abiotic factors, together to predict changes in community organization.